1976
DOI: 10.1104/pp.58.4.563
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis, Dark Respiration, and Growth of Rumex patientia L. Exposed to Ultraviolet Irradiance (288 to 315 Nanometers) Simulating a Reduced Atmospheric Ozone Column

Abstract: Net photosynthesis, dark respiration, and growth of Rumexpatientia L. exposed to a ultraviolet irradiance (288-315 nanometers) simulating a 0.18 atm-cm stratospheric ozone column were determined. The ultraviolet irradiance corresponding to this 38% ozone decrease from normal was shown to be an effective inhibitor of photosynthesis and leaf growth.The repressive action on photosynthesis accumulated through time whereas leaf growth was retarded only during the initial few days of exposure. Small increases in dar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
35
2

Year Published

1978
1978
1995
1995

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 125 publications
(43 citation statements)
references
References 25 publications
6
35
2
Order By: Relevance
“…Recent work has shown that enhanced UV-B (280-320 nm) radiation corresponding to global solar UV irradiance which would occur with a substantial atmospheric ozone reduction resulted in inhibition of photosynthesis and leaf growth (23). The effect on photosynthesis was cumulative, but the inhibition of leaf expansion was most pronounced during the first days of leaf expansion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that enhanced UV-B (280-320 nm) radiation corresponding to global solar UV irradiance which would occur with a substantial atmospheric ozone reduction resulted in inhibition of photosynthesis and leaf growth (23). The effect on photosynthesis was cumulative, but the inhibition of leaf expansion was most pronounced during the first days of leaf expansion.…”
mentioning
confidence: 99%
“…It appears that inhibition of expansion is not entirely due to reduction of photosynthetic rates (23). It is important to elucidate the physiological mechanisms involved in UV-B radiation inhibition of leaf expansion and how these may interact with mechanisms known to control leaf expansion.…”
mentioning
confidence: 99%
“…Recently, UV-B irradiation has been shown effective in inhibiting leaf expansion (22,29,30), seedling growth (1, 21), dark respiration (29), and ion transport (1), as well as altering membrane permeability (9-11). Ultraviolet-B radiation has also been shown to be a potent inhibitor of photosynthesis (4,5,16,26,29,30, 35) 4 To whom all correspondence should be addressed. (2,5,14), and electron transport (5,24,25).…”
mentioning
confidence: 99%
“…Recently, UV-B irradiation has been shown effective in inhibiting leaf expansion (22,29,30), seedling growth (1,21), dark respiration (29), and ion transport (1), as well as altering membrane permeability (9)(10)(11). Ultraviolet-B radiation has also been shown to be a potent inhibitor of photosynthesis (4,5,16,26,29,30,35) and a number of partial reactions of phytosynthesis, including Chl synthesis (2,14), the Hill reaction 'This work was performed with the support of National Aeronautics and Space Administration contract NAS9-15516, National Science Foundation grant SER77-06567, and by a grant from the Dean 4 To whom all correspondence should be addressed. (2,5,14), and electron transport (5,24,25).…”
mentioning
confidence: 99%
“…Photosynthesis (16,17), component reactions of photosynthesis (3), cell division rates (8), Chl concentrations (1), and plant growth (2) have been shown to be inhibited by exposure of plants to supplemental UV-B radiation. The degree of UV-B radiation-mediated inhibition appears to be species-dependent (7) and a function of the amount of UV-B radiation that penetrates plant leaves (14) and is absorbed by sensitive physiological molecules, such as proteins and nucleic acids.…”
mentioning
confidence: 99%